Theological Anthropology of Youth as the Paradigm for Youth Ministry - Noval, Christian (2018)
How we view youth influences how we engage in youth ministry. While social science is important for understanding young people, it cannot answer some questions that are significant for youth ministry: What is the role of youth as creature? What does it mean for our view of youth that we are God's children? How do we engage in youth ministry as a reflection of God's agape? Through a theological anthropology of youth formulated in light of how God relates to us, the Christian community might form a renewed youth ministry that goes beyond a one-way approach wherein youth ministry is reduced to simply trying to get young people to stick around. To understand the contribution of young people to the Christian community-beyond ensuring its future existence-we need to understand what "youth" is theologically. Using the thought of David Kelsey as a basis, the author formulates a theological anthropology of youth to present a theologically enriched view of youth that not only can guide how we think about youth ministry in general, but also aid in reflecting about young people with disabilities.
Keywords: David Kelsey; Youth Ministry; Creation; Perfection; Theological Anthropology